2014
DOI: 10.2308/ajpt-50882
|View full text |Cite
|
Sign up to set email alerts
|

Materiality Guidance of the Major Public Accounting Firms

Abstract: SUMMARY This paper examines the materiality guidance for eight of the largest U.S. public accounting firms. Knowledge of how materiality guidance is integrated into a firm's methodology is important for accounting and auditing researchers as well as for practitioners, regulators, and educators. Our results show a high level of consistency across the firms in terms of the quantitative benchmarks (e.g., income before taxes, total assets or revenues, and total equity) used to determine overall mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(115 citation statements)
references
References 19 publications
4
104
2
5
Order By: Relevance
“…The median amount of the impairment to the absolute value of income from continuing operations was 26.29%. Eilifsen and Messier (2015) examined the materiality guidance of eight of the largest public accounting firms and found that for determining the overall materiality of an item, the majority of the firms expect or require the use of 5% of income before taxes. Clearly, the goodwill impairments recorded by the Canadian companies in 2013 would be considered material (i.e., median impairment to income of 26.29%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The median amount of the impairment to the absolute value of income from continuing operations was 26.29%. Eilifsen and Messier (2015) examined the materiality guidance of eight of the largest public accounting firms and found that for determining the overall materiality of an item, the majority of the firms expect or require the use of 5% of income before taxes. Clearly, the goodwill impairments recorded by the Canadian companies in 2013 would be considered material (i.e., median impairment to income of 26.29%).…”
Section: Resultsmentioning
confidence: 99%
“…7, No. 9;2015 below-the-line item), companies with greater net worth covenant slack were more likely to record an impairment in the transition year than were firms with more binding covenants, who instead preferred to delay the expense recognition. In addition, they found evidence suggesting that the closer a company was to falling below the delisting threshold for its respective stock exchange, the less likely a goodwill impairment loss would be recorded.…”
Section: Literature Review and Development Of Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ANCOVA results in Panel A of Table 8 indicate significant main effects for ITEM (F (17,62237) = 146.82, p = 0.001) and SOURCE (F (2, 62237) = 2595.67, p = 0.001), indicating that data inconsistences among financial items and aggregators were significantly different. The results also show a significant interaction effect between SOURCE and ITEM (F (34,62237) = 222.41, p = 0.001), suggesting that the data differences for financial items differed in DataGuide, KisValue, and TS2000.…”
Section: Data Differences Among Aggregators and Financial Itemsmentioning
confidence: 90%
“…Based on Leslie [33] and Eilifsen and Messier [34], we define "material differences" as the degree to which absolute value differences are larger than 0.5% of Total Assets for balance sheet items and 5% of Earnings Before Interest and Taxes (EBIT) for income statement items except EPS; therefore, if the absolute value difference was larger than 0.5% of Total Assets or 5% of EBIT, then the variable was coded as 1; otherwise, it was coded as 0. For Earnings Per Share (EPS), we applied a materiality of 50 Korean Won (KRW); that is, if the material difference for EPS was greater than 50 KRW, then the variable was coded as 1; otherwise, it was coded as 0.…”
Section: Data Collection Procedures and Measuresmentioning
confidence: 99%